Directly Verifiable Neutron Diffraction Technique to Determine Retained Austenite in Steel. Issue 4 (30th October 2017) - Lychagina, Tatiana; Zisman, Alexander; Yashina, Ekaterina; Nikolayev, Dmitry
Abstract : Conventional procedures for quantitative analysis of retained austenite in steels by neutron diffraction ignore the effect of crystallographic texture and rely on a‐priori parameters rather than a direct calibration with appropriate etalons. As the main drawback, this method is not directly verified by independent data. In order to get over the verification problem, that is, to calibrate the method, reference sandwich‐like samples with predefined amounts of austenite have been prepared. Neutron diffraction allows to measure large samples from one hand and to get rid of the texture influence from the other. Application of the proposed method was illustrated by volume fractions of retained austenite determination in medium‐carbon martensitic steel tempered at various temperatures. Main result of our work is the developed method based on complete orientation averaging by means of neutron diffraction and usage of the calibration samples. It allowed to refine the austenite detectability limit to about 0.1% (vol.). Based on the method calibration, low fractions of retained austenite (0.13–2.9%) have been determined in the medium‐carbon martensitic steel tempered at various temperatures. Abstract : The new method of the quantitative analysis for retained austenite in steels by neutron diffraction is proposed. This approach is based on the calibration with reference samples in order to reliably evaluate low fractions of retained austenite in textured steels with detectability limit refined to 0.1%. The suggested method implies direct verification of the results.